2018
DOI: 10.1093/applin/amy005
|View full text |Cite
|
Sign up to set email alerts
|

Discipline, Level, Genre: Integrating Situational Perspectives in a New MD Analysis of University Student Writing

Abstract: While there have been many investigations of academic genres, and of the linguistic features of academic discourse, few studies have explored how these interact across a range of university student writing situations. To counter misconceptions that have arisen regarding student writing, this article aims to provide comprehensive linguistic descriptions of a wide range of university assignment genres in relation to multiple situational variables. Our new multidimensional (MD) analysis of the British Academic Wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(66 citation statements)
references
References 19 publications
5
59
1
1
Order By: Relevance
“…() employed the dimensions identified in Biber () to compare the linguistic characteristics of university spoken and written registers. This is the analytical approach that we adopt in the present study, employing the dimensions identified by Gardner, Biber, and Nesi (in press) based on analysis of the British Academic Writing in English (BAWE) Corpus. As we explain subsequently, we chose this approach because BAWE is by far the most comprehensive sample of university student writing in existence.…”
Section: Multi‐dimensional Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…() employed the dimensions identified in Biber () to compare the linguistic characteristics of university spoken and written registers. This is the analytical approach that we adopt in the present study, employing the dimensions identified by Gardner, Biber, and Nesi (in press) based on analysis of the British Academic Writing in English (BAWE) Corpus. As we explain subsequently, we chose this approach because BAWE is by far the most comprehensive sample of university student writing in existence.…”
Section: Multi‐dimensional Analysismentioning
confidence: 99%
“…Gardner et al. (in press) carried out an MD analysis based on the BAWE Corpus, describing the patterns of linguistic variation for university student writing across tasks (genres), disciplines, and academic levels. Here we simply provide an overview of the dimensions themselves.…”
Section: Multi‐dimensional Analysismentioning
confidence: 99%
“…In soft sciences, the researchers rarely deal with new phenomena in the discussion of their experiences, because they discuss the phenomena that are already familiar to us, re ecting little need for new technical vocabulary and complex grammatical constructions . In the same vein, Gardner et al (2019) argue that "hard sciences are more informational, while Humanities disciplines are more involved" (p. 3). This difference suggests that the writers in humanities disciplines tend to bolster their claims by more elaborated discussions through greater use of clausal features, while phrasal features used in hard sciences (especially pre-modi ers)…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a multidimensional analysis of university student writing (Gardner et al 2018), many engineering reports were found to express compressed procedural information through long scientific nominal groups (noun pre-modifiers, common, concrete, quantity nouns) and a focus on concisely reporting experimental procedures through passive action verbs. At the other end of this dimension Gardner et al (2018) find the "stance toward the work of others" that is typical of humanities essays, as evidenced through the absence of procedural features and the presence of 3rd person pronouns, stance nouns + that clauses, proper nouns, stance adverbials and communication verbs.…”
Section: Engineering Compared To Other Disciplinesmentioning
confidence: 99%
“…Differences have also been found across genres and levels of study, for instance between student reports and professional reports in civil engineering (Conrad 2017), between research articles and PhD theses (Koutsantoni 2006), between Master's and PhD dissertations in Hong Kong (Hyland 2004) and across levels of study at British universities both in lexical bundles (Durrant 2017) and grammatical features (Gardner et al 2018).…”
Section: Engineering Genres and Registers Comparedmentioning
confidence: 99%